UP Diliman Libraries' strategies for combating book theft, mutilation and vandalism - Bañez, Cecilia Poline D.G (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Library security has become a common overarching concern among librarians. Different strategies are employed in libraries to prevent or minimize cases of book theft, mutilation and vandalism